Motor unit behavior during submaximal contractions following six weeks of either endurance or strength training - Vila-Chã, Carolina (2011)
The study investigated changes in motor output and motor unit behavior following 6 weeks of either strength or endurance training programs commonly used in conditioning and rehabilitation. Twenty-eight sedentary healthy men (age, mean±SD, 26.1 ± 3.9 yrs) were randomly assigned to strength training (ST) (n = 9), endurance training (ET) (n = 10) or a control group (CT) (n = 8). Maximum voluntary contraction (MVC), time to task failure (isometric contraction at 30% MVC), and rate of force development (RFD) of the quadriceps, were measured before (week 0), during (week 3), and after a training program of 6 weeks. In each experimental session, surface and intramuscular EMG signals were recorded from the vastus medialis obliquus (VMO) and vastus lateralis (VL) muscles during isometric knee extension at 10% and 30% MVC. After 6 weeks of training, MVC and RFD increased in the ST group (17.5±7.5 % and 33.3±15.9 %, respectively; P < 0.05) whereas time to task failure was prolonged in the ET group (29.7±13.4 %; P < 0.05). Despite surface EMG amplitude during 30% MVC contractions increased following both training programs, there were different changes in motor unit discharge rates between the training groups. After endurance training, the motor unit discharge rate at 30% MVC decreased from 11.3 ±1.3 pulses per second (pps) to 10.1 ± 1.1 pps (P < 0.05) in the vasti muscles, whereas after strength training it increased from 11.4 ± 1.2 pps to 12.7 ± 1.3 pps (P < 0.05). Finally, motor unit conduction velocity during the contractions at 30% MVC increased for both the ST and ET groups, but only after 6 weeks of training (P < 0.05). In conclusion, strength and endurance training programs elicit opposite adjustments in motor unit discharge rates but similar changes in muscle fiber conduction velocity.